2019
DOI: 10.11606/issn.2316-9079.v18i1p115-121
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic position of two species of the Liolaemus elongatus-kriegi Complex and a new northern limit for L. buergeri (Squamata: Liolaemidae)

Abstract: Liolaemus is an extraordinarily diverse lizard genus containing 257 species (Abdala and Quinteros 2014). The genus has been split into several groups (e.g. Lobo et al. 2010) of which the L. elongatus-kriegi Complex (Cei 1979) is one of the most characteristic in the Patagonian region of Chile and Argentina (Esquerré et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In fact, all non‐genital traits in the L. elongatus group (with the exception of radius‐ulna length) presented low phylogenetic signal values, this indicated that could be under selective forces. The low divergence in genital morphology in the L. elongatus group could explain the hybridization processes between sympatric species, as was hypothesized by Troncoso‐Palacios et al (2019). Although is important to mention that in general L. elongatus group exhibits highly evolutionary patterns (Olave et al ., 2020).…”
Section: Discussionmentioning
confidence: 63%
“…In fact, all non‐genital traits in the L. elongatus group (with the exception of radius‐ulna length) presented low phylogenetic signal values, this indicated that could be under selective forces. The low divergence in genital morphology in the L. elongatus group could explain the hybridization processes between sympatric species, as was hypothesized by Troncoso‐Palacios et al (2019). Although is important to mention that in general L. elongatus group exhibits highly evolutionary patterns (Olave et al ., 2020).…”
Section: Discussionmentioning
confidence: 63%
“…Given that several lineages have been proposed as candidate species of the L. elongatus group through molecular phylogenetic studies (Morando et al, 2003;Medina et al, 2017;Troncoso-Palacios et al, 2018) whose taxonomic status remains undetermined and that several additional species of the group have been recently described (Troncoso-Palacios et al, 2018;Ruiz et al, 2019a;, this study), it is probable that the described diversity of this group of lizards will continue to increase in the coming years. For example, as was noted by Troncoso-Palacios et al (2019), it is needed a deeper study to clarify the taxonomic status of the population of lizards that occur in Altos de Lircay, Maule Region, which has been listed with several names: L. monticola Müller &Hellmich, 1932, L. carlosgarini, L. sp. 1 andL.…”
Section: Discussionmentioning
confidence: 99%